Universal simulation of absorption effects for X-ray diffraction in reflection geometry - Dallmann, Johannes; Graetz, Jonas; Hock, Rainer (Acta Crystallographica Section A : Foundations and Advances, 2024)
Analytical calculations of absorption corrections for X-ray powder diffraction experiments on non-ideal samples with surface roughness, porosity or absorption contrasts from multiple phases require complex mathematical models to represent their material distribution. In a computational approach to this problem, a practicable ray-Tracing algorithm is formulated which is capable of simulating angle-dependent absorption corrections in reflection geometry for any given rasterized sample model. Single or multiphase systems with arbitrary surface roughness, porosity and spatial distribution of the phases in any combination can be modeled on a voxel grid by assigning respective values to each voxel. The absorption corrections are calculated by tracing the attenuation of X-rays along their individual paths via a modified shear-warp algorithm. The algorithm is presented in detail and the results of simulated absorption corrections on samples with various surface modulations are discussed in the context of published experimental results.
CRIS-Team Scopus Importer:2024-07-19
Keywords: absorption corrections; microstructure; powder diffraction; ray-Tracing; surface roughness